Women, men and everyday talk - Coates, Jennifer; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
Bringing together a selection of some of the author's key papers on language and gender, this book provides an overview of the development of language and gender studies over the last 30 years, with particular emphasis on conversational data and on single sex friendship groups.
Keywords: Linguistics; Applied linguistics; Philology; Sociolinguistics; Discourse analysis; Social sciences; Linguistics; Applied Linguistics; Sociolinguistics; Discourse Analysis; Language and Literature; Social Sciences, general